2014
DOI: 10.1136/bjophthalmol-2013-304189
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive case series with long-term follow-up of full macular translocation for myopic choroidal neovascularisation

Abstract: FMT for mCNV maintained the improvement in VA for more than 5 years. However, postoperative complications and progression of chorioretinal atrophy due to myopia still seem to limit the visual improvement after FMT for mCNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nonetheless, in very select cases of mCNV refractory to anti-VEGF therapy, MT may be useful. Recently, Sakimoto et al 11 have reported the long-term effects of MT in a large consecutive case series of 60 eyes with mCNV that underwent MT (mean follow-up period: 76.3 months). They showed that the logarithm of the minimum angle of resolution (logMAR) BCVA values at 1 year, 3 years, and 5 years postoperatively significantly ( P <0.001) improved to 0.54 at 1 year and then remained stable.…”
Section: Current Treatment Options For Myopic Choroidal Neovascularizmentioning
confidence: 99%
“…Nonetheless, in very select cases of mCNV refractory to anti-VEGF therapy, MT may be useful. Recently, Sakimoto et al 11 have reported the long-term effects of MT in a large consecutive case series of 60 eyes with mCNV that underwent MT (mean follow-up period: 76.3 months). They showed that the logarithm of the minimum angle of resolution (logMAR) BCVA values at 1 year, 3 years, and 5 years postoperatively significantly ( P <0.001) improved to 0.54 at 1 year and then remained stable.…”
Section: Current Treatment Options For Myopic Choroidal Neovascularizmentioning
confidence: 99%
“…Sakimoto2 and colleagues report 60 eyes with a mean of 72 months follow-up after full macular translocation for myopic choroidal neovascularization. There was a significant improvement in the logMAR best corrected visual acuity from 0.78 to 0.54, 0.57 and 0.61 at 1, 3 and 5 years respectively.…”
Section: Long-term Follow-up Of Full Macular Translocation For Myopicmentioning
confidence: 99%